2018
DOI: 10.3390/md16010024
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antioxidant Capacities and Attenuation of Lipid Accumulation in 3T3-L1 Adipocytes by Low-Molecular-Weight Fucoidans Prepared from Compressional-Puffing-Pretreated Sargassum Crassifolium

Abstract: In this study, we extracted fucoidan from compressional-puffing-pretreated Sargassum crassifolium by hot water. The crude extract of fucoidan (SC) was degraded by various degradation reagents and four low-molecular-weight (LMW) fucoidans, namely SCO (degradation by hydrogen peroxide), SCA (degradation by ascorbic acid), SCOA (degradation by hydrogen peroxide + ascorbic acid), and SCH (degradation by hydrogen chloride) were obtained. The degradation reagents studied could effectively degrade fucoidan into LMW f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…In agreement with our finding, a reduced viability in rat adrenal pheochromocytoma cells subjected to H 2 O 2 was attenuated, when treating cells with 30 and 60 µg/mL fucoidan [19]. In the current research, however, the treatment of IPEC-1 cells that suffered oxidative stress with 100 or 200 µg/mL fucoidan actually did not exert a protective effect, which may be pertinent to the cytotoxicity of fucoidan at higher doses [23]. Likewise, Jeong et al [42] observed that the administration of 50 µg/mL fucoidan alleviates 5-fluorouracil-induced cell growth inhibition in dendritic cells, but a high level of fucoidan (100 µg/mL) exhibits a slight cytotoxicity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with our finding, a reduced viability in rat adrenal pheochromocytoma cells subjected to H 2 O 2 was attenuated, when treating cells with 30 and 60 µg/mL fucoidan [19]. In the current research, however, the treatment of IPEC-1 cells that suffered oxidative stress with 100 or 200 µg/mL fucoidan actually did not exert a protective effect, which may be pertinent to the cytotoxicity of fucoidan at higher doses [23]. Likewise, Jeong et al [42] observed that the administration of 50 µg/mL fucoidan alleviates 5-fluorouracil-induced cell growth inhibition in dendritic cells, but a high level of fucoidan (100 µg/mL) exhibits a slight cytotoxicity.…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, Roy Chowdhury et al [20] found that a bacterial fucose-rich polysaccharide protects human lung fibroblast cells against H 2 O 2 -induced apoptosis and necrosis by directly scavenging ROS. The biological function of fucoidan against oxidative stress has also been reported in mesenchymal stem cells [21], normal human hepatocytes [22], and mouse adipocytes [23]. Michel et al [24] initially showed that fucoidan is totally excreted after oral administration, since it cannot be fermented by intestinal bacterial flora in humans.…”
Section: Introductionmentioning
confidence: 98%
“…Ale et al published comprehensive articles discussing the history of extraction, including the different classical extraction methods of fucoidans, and reported that extraction procedures significantly affect the polymers monomeric composition, even for the same organism [60,115]. Beyond simple hot water extraction [58,116], attempts were made to increase the selectivity and extraction yields, including extraction in acidic [117], alkaline [118], and buffered [41,119] aqueous solutions. However, a neutralization step is required, using Na 2 CO 3 or (NH 4 ) 2 CO 3, directly after extraction to guard against the non-specific acidic hydrolysis of the polymer [101,115].…”
Section: Extractionmentioning
confidence: 99%
“…Owing to their high molecular weight, therapeutic applications of native fucoidans face many challenges including structure elucidation, solubility, manufacturing, and handling [63,116], in addition to safety as a food supplement [175]. Structure elucidation and quantitation of native fucoidans is highly complicated and requires advanced or hyphenated spectroscopic techniques such asHPLC-MS/MS as it applied in Sea Cucumbers fucoidans [176,177].…”
Section: Enzymatic Modification Of Native Fucoidansmentioning
confidence: 99%
“…While Sargassum sp. has resistance against Propionibacterium acnes, S. epidermidis, Pseudomonas aeruginosa, E. coli and S. aureus (Kim et al, 2016;Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%